Codebuster. - Kushner, D.
The paper presents a brief biography of Andy Clarke who is currently a director of Inforenz.
Keywords: Andy Clark; Deep Thought; Inforenz; Codes; Computer crime; Computer forensics; Data encryption; Decryption technique; Parallel computers